Body Sensor Networks - Yang, Guang-Zhong (Springer London : Imprint: Springer, 2006)
The last decade has witnessed a rapid surge of interest in new sensing and monitoring devices for healthcare. One key development in this area is wireless wearable and implantable in vivo monitoring and intervention devices. While the problems of long-term stability and biocompatibility are being addressed, several promising prototypes are starting to emerge for managing patients with acute diabetes, for treatment of epilepsy and other debilitating neurological disorders and for monitoring of patients with chronic cardiac diseases. Despite the technological developments in sensing and monitoring devices, issues related to system integration, sensor miniaturization, low-power sensor interface circuitry design, wireless telemetric links and signal processing still have to be investigated. This book addresses the general issues related to the rapidly changing field of Body Sensor Networks (BSN) and discusses the latest technological developments and potential clinical applications. Key contents of the book include: Biosensor Design, Interfacing and Protein Engineering Wireless Communication and Network Topologies Communication Protocols and Standards Energy Scavenging Ultra-Low Power Bio-inspired Processing Multi-sensor Fusion and Context-aware Sensing Autonomic Sensing System Integration and Wireless sensor Microsystem Design The book also provides a comprehensive review of current wireless sensor development platforms and a step-by-step guide to developing your own BSN applications through the use of the BSN Development Kit. Online materials and the latest updates for the BSN Development Kit are available from http://www.bsn-web.info.